PENINGKATAN HASIL BELAJAR JURNAL PENYESUAIAN MELALUI MODEL PEMBELAJARAN LANGSUNG DENGAN PENDEKATAN FLIPPED CLASSROOM - Robertus Romy Siga (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This research aimed to find out the increasing of learning outcomes in adjusting journal entry, the teacher’s activities of instructional management, and the student’s activities in learning process at  XII-IPS3 classes of SMA Negeri 3 Tarakan in the academic year 2021/2022. The type of this research was classified as Classroom Action Research (CAR) by applied the direct instruction by the flipped classroom approach. The result of this analysis showed that both  teacher’s and student’s activities indicated gradual increases in the three cycles. Student’s learning outcomes also went up in each cycle. The observation of teacher’s activities in the first cycle was 3,78 and become 4,12 in the second cycle, and went up to 4,43 in the third cycle while in observation of student’s activities in the first cycle was 2,95 and become 3,45 in the second cycle and went up to 3,60 in the third cycle.  Classically, passing rates in the  first cycle was 41,66% and in the second cycle, it increased by 69,44%  and went up to 88,89% in the third cycle. The strength in learning by the direct instruction and the flipped classroom approach were it can improved teacher’s activities, student’s activities and  learning outcomes. While the weaknesses were it need more time to prepare the subject, and the student with inadequacy in motivation unable to follow the lessons. Based on the result of this research  it could be inffered,  the direct instruction and the flipped classroom approach are eligible in improving the student learning outcomes in adjusting entries